Improving the load flexibility of industrial air separation units using a pressure‐driven digital twin. Issue 7 (31st March 2022) - Kender, Robert; Rößler, Felix; Wunderlich, Bernd; Pottmann, Martin; Thomas, Ingo; Ecker, Anna‐Maria; Rehfeldt, Sebastian; Klein, Harald
Abstract: Air separation units are one of the prime examples for studies on demand side management and (non‐)linear model predictive control due to their high power consumption and energy storage potential. These plants separate ambient air into its main components, nitrogen, oxygen, and argon, by means of cryogenic distillation at different pressure levels. Approximately two thirds of the industrially operated air separation units consider the separation of argon either as a value product or for reasons of energy efficiency. However, most of the studies in literature neglect the separation of argon since this requires additional equipment, increases the heat and process integration and, thus, the complexity of process control. In this work, a digital twin of an air separation unit with argon system is used to analyze and to improve load change procedures. Moreover, the potential of applying the digital twin as a soft sensor is demonstrated.